WHAT LIES BEYOND STREAKS AND BADGES? DUOLINGO’S GAMIFICATION STRATEGY AND ITS LIMITATIONS - Bastiaan, Rachel Getroida; Rumokoy, Lawren Julio; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2024)
The use of gamification has become prominent in marketing especially after the pandemic, where people are often not satisfied with just the normal experience. This need and craving for a personalized engaging experience in each person are leading to a tight competition between businesses to leave the most valuable experience for users. Duolingo has proven to be a market leader within language-learning apps and has retained, also increased loyal customers over the years with the use of gamification. Despite the visible success of gamification in different fields and its importance in today’s market, the language-learning app is rarely discussed in a marketing context. This study explores the implementation of gamification by one of its earliest adopters and the limits to this strategy itself. Using phenomenology method and thematic analysis, this qualitative study inquired 20 users of Duolingo using semi-structured interviews. Results showed how intrinsic motivation played a big role in loyal users and Duolingo supported those intrinsic motivation to gather customers and create a more enjoyable way of learning with gamification. With limitations mostly coming because of personal priorities as hindrance and not due to the app lacking itself. Keywords: Gamification, Marketing, Immersive Experience